The Role of Professional Ethics, Competence, Job Satisfaction and Work Motivation on Teacher Performance - Apriani Riyanti (Journal on Education, 2023)
motivation, competence, and job satisfaction. Private schools were used for the research. There were 54 participants in the entire population that participated in the survey as respondents. The information was gathered through the use of a questionnaire, which involved providing the respondents with a series of statements. Multiple linear regression was the method of data analysis employed in this study, and it was carried out using the SPSS 17 program at a significance level of 5%. The simultaneous f test findings demonstrate that teacher performance is significantly influenced by professional ethics, motivation, competence, and job satisfaction. The t (partial) test results demonstrate that teacher performance is highly influenced by professional ethics, motivation, competence, and job satisfaction. So, it may be stated that teacher performance is greatly influenced both simultaneously and partially by professional ethics, motivation, competence, and job satisfaction.